Safety and efficacy of topiramate in neonates with hypoxic ischemic encephalopathy treated with hypothermia (NeoNATI): a feasibility study. (18th April 2018) - Filippi, Luca; Fiorini, Patrizio; Catarzi, Serena; Berti, Elettra; Padrini, Letizia; Landucci, Elisa; Donzelli, Gianpaolo; Bartalena, Laura; Fiorentini, Erika; Boldrini, Antonio; Giampietri, Matteo; Scaramuzzo, Rosa Teresa; et al.
Abstract: Purpose: To investigate the feasibility of a study based on treatment with topiramate (TPM) added to moderate hypothermia in newborns with hypoxic ischemic encephalopathy (HIE). Materials and methods: Multicenter randomized controlled trial. Term newborns with precocious metabolic, clinical and electroencephalographic (EEG) signs of HIE were selected according to their amplified integrated EEG pattern and randomized to receive either TPM (10 mg/kg once a day for the first three days of life) plus moderate hypothermia or hypothermia alone. Safety was assessed by monitoring cardiorespiratory parameters and blood samples collected to check renal, liver, metabolic balance and TPM pharmacokinetics. Efficacy was evaluated by the combined frequency of mortality and severe neurological disability as primary outcome. Incidence of magnetic resonance injury, epilepsy, blindness, hearing loss, neurodevelopment at 18–24 months of life was assessed as secondary outcomes. Results: Forty-four asphyxiated newborns were enrolled in the study. Twenty one newborns (10 with moderate and 11 with severe HIE) were allocated to hypothermia plus TPM and 23 (12 moderate and 11 severe HIE) to hypothermia. No statistically or clinically significant differences were observed for safety, primary or secondary outcomes. However, a reduction in the prevalence of epilepsy was observed in newborns co-treated with TPM. Conclusions: Results of this pilot trial suggest that administration of TPM in newborns with HIE is safe but does not reduce the combined frequency of mortality and severe neurological disability. The role of TPM co-treatment in preventing subsequent epilepsy deserves further studies.